2014
DOI: 10.1124/dmd.114.057216
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger Nuclease–Mediated Gene Knockout Results in Loss of Transport Activity for P-Glycoprotein, BCRP, and MRP2 in Caco-2 Cells

Abstract: Membrane transporters P-glycoprotein [P-gp; multidrug resistance 1 (MDR1)], multidrug resistance-associated protein (MRP) 2, and breast cancer resistance protein (BCRP) affect drug absorption and disposition and can also mediate drug-drug interactions leading to safety/toxicity concerns in the clinic. Challenges arise with interpreting cell-based transporter assays when substrates or inhibitors affect more than one actively expressed transporter and when endogenous or residual transporter activity remains foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 47 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…It is of interest to note that the ER values of fexofenadine and digoxin measured by Caco‐2 cell assay were much greater than those by MDR1‐MDCK cell assay. It is well known that Caco‐2 cells express many major efflux transporters, including P‐gp, BCRP, and MRPs 31‐33 . These results suggest that fexofenadine and digoxin are not only substrates of P‐gp but also substrates of other efflux transporters, possibly BCRP and/or MRPs.…”
Section: Resultsmentioning
confidence: 84%
“…It is of interest to note that the ER values of fexofenadine and digoxin measured by Caco‐2 cell assay were much greater than those by MDR1‐MDCK cell assay. It is well known that Caco‐2 cells express many major efflux transporters, including P‐gp, BCRP, and MRPs 31‐33 . These results suggest that fexofenadine and digoxin are not only substrates of P‐gp but also substrates of other efflux transporters, possibly BCRP and/or MRPs.…”
Section: Resultsmentioning
confidence: 84%
“…To further evaluate the relative contribution of P-gp and BCRP in the efflux of EPAC in Caco-2 cells, we conducted an additional study in MDR1/MRP2 double-KO and BCRP/MRP2 double-KO Caco-2 cell lines. It has been demonstrated that these KO cell lines, derived from Caco-2 cells (C2BBe1 clone), are similar to the wild type Caco-2 cells with respect to growth rate, morphology, differentiation, tight junction formation, passive permeability of model compounds, and stability of phenotype (Sampson et al, 2015). Two control substrates, digoxin (P-gp substrate) and estrone sulfate (BCRP substrate), were used in this study to ensure the validity of these KO models.…”
mentioning
confidence: 99%
“…The Caco-2-kh cell line may not be an unusual cell line since another subclone of Caco-2 cells, which showed the characteristics of matured intestinal epithelial cells from the beginning of culture, has also been reported (Sampson et al, 2015). This feature of the Caco-2-kh cell line allowed us to examine the uptake of Cd in the trans-well culture system within a few days after the introduction of siRNAs of metal transporters.…”
Section: Transport From the Apical Membrane Of Caco-2-kh Cellsmentioning
confidence: 99%